Investment in ICT: Determinants and Economic Implications - Nadine Fabritz (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2015)
This study was prepared by Nadine Fabritz while she was working at the Ifo Institute for Economic Research in the Department for Human Capital and Innovation. It was completed in June 2014 and accepted as a doctoral thesis by the Department of Economics at the University of Munich in October 2014. It consists of four distinct empirical analyses in the field of the economics of Information and Communication Technologies (ICT). Three analyses address the economic effects of ICT investments, while one is concerned with determinants of investment in ICT networks. The study uses German firm-level data and regional-level data from Germany and the United Kingdom. The empirical strategies in all analyses attempt to establish causal relationships between the variables and outcomes of interest as much as possible by using panel models and controlling for unobserved, timeinvariant individual factors.
Keywords: L50; L96; O10; O30; R10; 330; Innovation; Informationstechnik; Breitbandkommunikation; Infrastrukturinvestition; Investition; Regionalentwicklung; Regulierung; Computerunterstützung; Produktentwicklung; Unternehmenserfolg; Theorie; Schätzung; Deutschland; Großbritannien; Informationstechnik; Investition; Computerunterstützung; Produktentwicklung; Unternehmenserfolg; Breitbandkommunikation; Infrastrukturinvestition; Deregulierung; Ländliche Entwicklung; Theorie; Schätzung; Deutschland; Großbritannien